Optimization of dangerous goods transport in urban zone - Ebrahimi, Hamid; Tadic, Milos (Decision Making: Applications in Management and Engineering, 2018)
Due to the specificity of the transport of dangerous goods, as well as the obligations arising from the legislation regulating this field, all the actors of this process are obliged to take special measures in order to avoid undesired consequences. Special attention is paid to the planning of the transport of dangerous goods. One of the most important planning elements is choosing a route for the transport of dangerous goods in urban areas. In order to take preventive measures, risk assessment is carried out on the routes and the minimum risk route is defined. In this paper, a new model for selection of the routes for the transport of dangerous goods (hazmat) on the network of urban roads is proposed. The model is based on a multi-criteria risk analysis and the traditional Dijkstra algorithm (D-R model). The D-R model is a new approach for minimizing the cost and a variety of risk criteria in hazmat routing, which adequately takes into account and minimizes a number of risks on potential routes. The model is based on route selection based on the absolute risk size. The proposed routing model was tested in a real case and in a real urban hazmat routing problem, in Serbia.